问题 解答题
下面各题,怎样简便就怎样算:
(1)
2
9
÷5+
1
5
×
7
9
(2)
5
4
-
9
10
×
7
9
-
3
10
(3)
4
15
×[(
3
4
-
7
12
)÷
4
9
]
(4)
7
10
÷(
4
3
-
2
5
)×
4
9
答案

(1)

2
9
÷5+
1
5
×
7
9

=

2
9
×
1
5
+
1
5
×
7
9

=(

2
9
+
7
9
)×
7
9

=1×

7
9

=

7
9

(2)

5
4
-
9
10
×
7
9
-
3
10

=

5
4
-
7
10
-
3
10

=

5
4
-(
7
10
+
3
10
),

=

5
4
-1,

=

1
4

(3)

4
15
×[(
3
4
-
7
12
)÷
4
9
],

=

4
15
×[(
9
12
-
7
12
)×
9
4
],

=

4
15
×[
1
6
×
9
4
],

=

4
15
×
3
8

=

1
10

(4)

7
10
÷(
4
3
-
2
5
)×
4
9

=

7
10
÷(
20
15
-
6
15
)×
4
9

=

7
10
÷
14
15
×
4
9

=

7
10
×
15
14
×
4
9

=

1
3

选择题
单项选择题